(untitled) (Proceedings of International Educators Conference, 2024)
Artificial Intelligence (AI) is revolutionizing education by offering personalized learning experiences, enhancing teaching methods, and transforming traditional classroom dynamics. This article explores the significance of AI in education, examines its current applications, and discusses its potential future impact. Through a literature review, it evaluates the effectiveness of AI-driven educational tools and methodologies. The methods section outlines various AI technologies utilized in education, while the results section presents examples of successful AI implementations. Finally, the discussion section analyzes the implications of AI in education and offers insights into its future trajectory.